The Impact Of Tide On Flooding In The The Kali Welang, Pasuruan, East Java - Ainun M. M. Gasa; Umboro Lasminto (Journal of Civil Engineering, 2025)
Flooding in the Welang River, Pasuruan, East Java, is a recurrent problem influenced by multiple factors, primarily high-intensity rainfall and tidal fluctuations. This study aims to quantitatively assess the impact of tidal conditions—including extreme events such as supermoons—on the spatial extent and depth of flood inundation in the downstream segment of the Welang River. Utilizing hydrologic (HEC-HMS) and hydraulic (HEC-RAS) modeling, the research estimates design flood discharges for multiple return periods and simulates three scenarios: (1) flood discharge without tidal influence, (2) flood discharge under normal tidal conditions, and (3) flood discharge during tidal peaks associated with a supermoon. The results indicate that the 100-year design discharge reaches 409.7 m³/s. Tidal conditions significantly amplify both the extent and depth of inundation, with the greatest increase in flood coverage observed at the 2-year return period (85.88%). Furthermore, the supermoon phenomenon intensifies flooding, producing the highest additional inundation extent during the 5-year return period (34.81%).